Implementasi SPK Karyawan Terbaik Metode A-Hirarki Proses dan S-Additive Weighting - Wawan Taufiq Wawan; Supriyanto Supriyanto; Sidik Rahmatullah (Institut Informatika dan Bisnis Darmajaya, 2023)
PT. Puncak Menara Hijau Mas Kotabumi is an industrial company engaged in the wood processing business. This company processes wood into 4 kinds of materials which are ready to be supplied to Java Island and some are exported to Japan. The 4 types of processed wood produced are Sawntimber ex KD, S4S (4-sided shaved), Plywood and Furniture. In order to increase the quality of decisions, decision support systems combine various intelligence sources. We use 2 methods, namely AHP and SAW, weight Criteria1 16%, Criteria 2 33%, Criteria 3 13%, Criteria 4 11%, Criteria 5 6%,, Criteria 6 17%, Criteria 7 4% The final result of the employee who is given the best predicate is Alternative 47 with a rank of 2,049 . So that the employee is entitled to get a prize/bonus as the best employee